Rail Transport and Firm Productivity : Evidence from Tanzania - Iimi, Atsushi; Humphreys, Richard Martin; Mchomvu, Yonas Eliesikia (World Bank, Washington, DC, 2017)
Railway transport generally has the advantage for large-volume, long-haul freight operations. Africa possesses significant railway assets. However, many rail lines are currently not operational because of the lack of maintenance. The paper recasts light on the impact of rail transportation on firm productivity, using micro data collected in Tanzania. To avoid the endogeneity problem, the instrumental variable technique is used to estimate the impact of rail transport. The paper shows that the overall impact of rail use on firm costs is significant despite that the rail unit rates are set lower when the shipping distance is longer. Rail transport is a cost-effective option for firms. However, the study finds that firms' inventory is costly. This is a disadvantage of using rail transport. Rail operations are unreliable, adding more inventory costs to firms. The implied elasticity of demand for transport services is estimated at -1.01 to -0.52, relatively high in absolute terms. This indicates the rail users' sensitivity to prices as well as severity of modal competition against truck transportation. The study also finds that firm location matters to the decision to use rail services. Proximity to rail infrastructure is important for firms to take advantage of rail benefits.